Fathers Involvement In Maternal Health: Need Of Father’s Friendly SRHR Consultation Services In Rural Bangladesh - Rahman, Tahia; Khan, Ishrat (2016)
This article deals with the need of father friendly SRHR services to ensure maternal health in rural community. Using qualitative research methods this research tries to evaluate whether consultation service on SRHR (Sexual and Reproductive Health and Rights) by the Health Service providers increases men’s involvement in maternal health care in northern Bangladesh. The first part deals with the background and contexts of the paper shedding light on the traditional practices of fatherhood in relation to maternal health care in rural Bangladesh. It shows that fathers traditionally denies to take part in maternal care issues even though there is a huge network of Maternal Care established by the government of Bangladesh. The second part of this paper describes the process of sensitizing the health service providers designed by CMMS and Promundu US so that they set up father friendly SRHR (Sexual and Reproductive Health and Rights) consultation services to encourage and engage fathers in maternal care. The third part deals with the specific cases of fathers who were motivated by the health service providers and took part in maternal health care. Based on these cases in the conclusion the paper argues that father friendly consultation services can increase their involvement in maternal health services that ultimate results in improved maternal health.